"A Church, A Bar, and A Brewery" : Prohibition and Ethno-Religious Identities in Berlin, Wisconsin, 1910-1933 - Schroeder, Danielle Ann; Oberly, James Warren, 1954- (My University, 2017)
This research studies how the residents of Berlin—a small, central-northeastern Wisconsin city with a heavy German-Polish population—reacted to Prohibition. Religious, ethnic, and class identities play a significant role in Americans’ relationship with alcohol and drinking.
Color poster with text, maps, charts, and images.
Keywords: Berlin (Wis.); Polish immigrants; German immigrants; Prohibition; Posters